Pengaruh Disiplin Kerja dan Pelatihan Kerja Terhadap Kinerja Karyawan pada Peterseli Kitchen Pekanbaru - Desvi Emti; Dina Salimah; Yantos (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to determine the effect of Work Discipline and Job Training on Employee Performance at Peterseli Kitchen Pekanbaru. This study uses a quantitative descriptive method that describes the variables as they are and is supported by data in the form of numbers generated from actual circumstances. The data used are primary data and secondary data. The population in this study amounted to 38 people and the sample used in this study amounted to 38 people. The results showed that work discipline affects employee performance, as well as job training affects employee performance at Peterseli Kitchen Pekanbaru. Work Discipline and Job Training affect Employee Performance at Peterseli Kitchen Pekanbaru. The amount of influence is shown by the coefficient of determination of 51.1%, this shows that as much as 51.1% of employee performance is influenced by work discipline and job training and as much as 48.9% is influenced by other variables not examined in this study.